2009
DOI: 10.5194/bg-6-479-2009
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of microbes, organic aerosols, dust, sea-salt Na ions, non-sea-salt Ca ions, and methanesulfonate onto Greenland and Antarctic ice

Abstract: Abstract. Using a spectrofluorimeter with 224-nm laser excitation and six emission bands from 300 to 420 nm to measure fluorescence intensities at 0.3-mm depth intervals in ice cores, we report results of the first comparative study of concentrations of microbial cells (using the spectrum of proteinbound tryptophan (Trp) as a proxy) and of aerosols with autofluorescence spectra different from Trp (denoted "nonTrp") as a function of depth in ice cores from West Antarctica (WAIS Divide and Siple Dome) and Greenl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The mean stream water concentrations of ∼ 3 × 10 4 biological particles ml −1 and ∼ 2 × 10 4 cells ml −1 corresponds to published values for bacteria and/or cell abundance in glacial meltwaters at ML (Anesio et al ., ; Mindl et al ., ; Rassner, ); the range of ice core cell concentrations found in the MLSG catchment of 1.83 × 10 4 –2.25 × 10 5 cells ml −1 lie well within published in‐ice concentrations ranging from 7.0 × 10 2 to 1.4 × 10 7 cells ml −1 (Miteva and Brenchley, ; Price et al ., ). The proportion of cells within the aeolian samples was broadly similar to those in ice and stream samples, a finding reiterated by Segawa and colleagues () who reported the delivery and elution of microbes from a mountain snowpack, and Hawes's () indication that the southerly winds, which characterize the ML catchment, deliver organic material to the local terrain surface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean stream water concentrations of ∼ 3 × 10 4 biological particles ml −1 and ∼ 2 × 10 4 cells ml −1 corresponds to published values for bacteria and/or cell abundance in glacial meltwaters at ML (Anesio et al ., ; Mindl et al ., ; Rassner, ); the range of ice core cell concentrations found in the MLSG catchment of 1.83 × 10 4 –2.25 × 10 5 cells ml −1 lie well within published in‐ice concentrations ranging from 7.0 × 10 2 to 1.4 × 10 7 cells ml −1 (Miteva and Brenchley, ; Price et al ., ). The proportion of cells within the aeolian samples was broadly similar to those in ice and stream samples, a finding reiterated by Segawa and colleagues () who reported the delivery and elution of microbes from a mountain snowpack, and Hawes's () indication that the southerly winds, which characterize the ML catchment, deliver organic material to the local terrain surface.…”
Section: Discussionmentioning
confidence: 97%
“…The latter, here classed as 'residual biological fraction', was suggestive of a particulate population comprising fragmented or degraded cells or nucleic acids (DNA/RNA), or viral particles. Support for this interpretation is given by virus geometries and fluorescence signals (Brussaard et al, 2000), supraglacial viral abundance observed proximate to MLSG (Rassner, 2009) and potential fluorescent 'noise' associated with organic, non-cellular particulates and aerosols found within glacier ice (Price et al, 2009). Setting gates to define cells, these were then differentiated by size: size categories were defined using 0.5, 0.9 and 3 mm Megamix (BioCytex, France) fluorescent beads (Fig.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…From ∼ 20 to ∼ 100 times as many dust grains are deposited in polar ice during glacial maxima as in glacial minima. During the Holocene (the present warm period) the average dust concentration has been 40 to 50 ng g −1 in Greenland ice and ∼ 10 ng g −1 in Antarctic ice (Price et al, 2009). In a detailed study of dust in the NGRIP Greenland core with a laser microparticle detector, Ruth et al (2003) measured log normal modes of 1.3 µm during the Holocene and 1.7 µm during the LGM.…”
Section: Flow Cytometry Of Weakly Fluorescent Mineral Grainsmentioning
confidence: 99%
“…In the present work we used that same instrument to map Chl in ice cores by analysing the two channels at 670 and 710 nm. Price et al (2009) determined the concentrations of non-microbial aerosols from the deviations of their fluorescence spectra from the spectrum of Trp, which has a peak at ∼ 320 nm when bound in cells. In Table 1 we note that Antarctic ice has a lower concentration of all small particles by a factor of several than Greenland ice.…”
Section: Flow Cytometry Of Weakly Fluorescent Mineral Grainsmentioning
confidence: 99%
See 1 more Smart Citation